Imaging biomarkers in neurodegeneration: current and future practices - Peter N. E. Young; Mar Estarellas; Emma Coomans; Meera Srikrishna; Helen Beaumont; Anne Maass; Ashwin V. Venkataraman; Rikki Lissaman; Daniel Jiménez; Matthew J. Betts; Eimear McGlinchey; David Berron; et al. (Alzheimer’s Research & Therapy, 2020)
Abstract There is an increasing role for biological markers (biomarkers) in the understanding and diagnosis of neurodegenerative disorders. The application of imaging biomarkers specifically for the in vivo investigation of neurodegenerative disorders has increased substantially over the past decades and continues to provide further benefits both to the diagnosis and understanding of these diseases. This review forms part of a series of articles which stem from the University College London/University of Gothenburg course “Biomarkers in neurodegenerative diseases”. In this review, we focus on neuroimaging, specifically positron emission tomography (PET) and magnetic resonance imaging (MRI), giving an overview of the current established practices clinically and in research as well as new techniques being developed. We will also discuss the use of machine learning (ML) techniques within these fields to provide additional insights to early diagnosis and multimodal analysis.